Pharmacological Characterization of the Mechanisms Involved in Delayed Calcium Deregulation in SH-SY5Y Cells Challenged with Methadone - Sergio Perez-Alvarez; Maria E. Solesio; Maria D. Cuenca-Lopez; Raquel M. Melero-Fernández de Mera; Carlos Villalobos; Hanna Kmita; Maria F. Galindo; Joaquin Jordán (International Journal of Cell Biology)
Previously, we have shown that SH-SY5Y cells exposed to high concentrations of methadone died due to a necrotic-like cell death mechanism related to delayed calcium deregulation (DCD). In this study, we show that, in terms of their Ca2+ responses to 0.5 mM methadone, SH-SY5Y cells can be pooled into four different groups. In a broad pharmacological survey, the relevance of different Ca2+-related mechanisms on methadone-induced DCD was investigated including extracellular calcium, L-type Ca2+ channels, μ-opioid receptor, mitochondrial inner membrane potential, mitochondrial ATP synthesis, mitochondrial Ca2+/2Na+-exchanger, reactive oxygen species, and mitochondrial permeability transition. Only those compounds targeting mitochondria such as oligomycin, FCCP, CGP 37157, and cyclosporine A were able to amend methadone-induced Ca2+ dyshomeostasis suggesting that methadone induces DCD by modulating the ability of mitochondria to handle Ca2+. Consistently, mitochondria became dramatically shorter and rounder in the presence of methadone. Furthermore, analysis of oxygen uptake by isolated rat liver mitochondria suggested that methadone affected mitochondrial Ca2+ uptake in a respiratory substrate-dependent way. We conclude that methadone causes failure of intracellular Ca2+ homeostasis, and this effect is associated with morphological and functional changes of mitochondria. Likely, this mechanism contributes to degenerative side effects associated with methadone treatment.